Konstruksi Feminisme dalam Film Little Women : (Sebuah Studi Komunikasi) - Clara Yunita Afdiani; Oemi Hartati; Diryo Suparto (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
This research investigates the construction of feminism in the film Little Women and its signs. Using descriptive qualitative methods and data collection techniques, the author uses Charles Sander Pierce's semiotic analysis and Mc Call's inter-categorical intersectional approach to group scenes and captures. The study reveals 19 scenes and 73 images containing feminism. The first concept of feminism, Stereotype classification, which forms individual opinions (Labelling), has the most sub-classifications, with seven. The research reveals that society created numerous labels for women, covering various aspects of life, including attitudes, behavior, politeness, appearance, and rights. These stereotypes reflect helplessness and perceived injustice, as perceived injustice comes from society itself. The research concludes that feminism in Little Women is a complex concept with multiple sub-classifications.